The Effectiveness Of Papaya Leaf Decoction On Young Women Against Dysmenorrhea During Menstruation In MTS. Annur Of Aek Corsik Village In 2021 - Maidina Putri; Afriyol Nelis (Institute of Computer Science (IOCS), 2021)
Menstruation is one of the aspects of sexual maturity that first occurs during puberty of a woman. Menstruation (menstruation) is periodic and cyclic bleeding from the uterus accompanied by the release (desquamation) of the endometrium. Menstruation (menstruation) accompanied by pain (Dysmenorrhea) is abdominal pain that comes from uterine cramps that occur during menstruation. According to WHO (Word Human Organization) the incidence of dysmenorrhea in Indonesia is 64.25%, consisting of 54% primary dysmenorrhea and 9.36% secondary dysmenorrhea. Handling dysmenorrhea by giving analgesic drugs as symptomatic (pharmacological) and non-pharmacological therapy, namely drinking papaya leaf decoction. This research is a type of quantitative research with a quasi-experimental one group pre post test method without control. Research with a group design of subjects was given an intervention without any comparison. This research was conducted at MTs An-Nur in Aek Korsik village in 2021, with a population of 72 students and a sample of 30 respondents. The sampling technique uses quota sampling. Data collection The intensity of dysmenorrhea using the Numerical Rating Scale (NRS), statistical analysis of the data using the paired sample T-Test test obtained that the average level of menstrual pain (dysmenorrhea intensity) or the mean before being given papaya leaf decoction was 4.70. Then there was a decrease for the average intensity of dysmenorrhea or the mean after being given papaya leaf decoction to 3.20 and the p-value was 0.000 <0.05 (p = 0.000 <0.05). The conclusion is that there is effectiveness of papaya leaf decoction in adolescent girls against dysmenorrhea during menstruation in MTs. Annur of Aek Korsik Village, so that it is hoped that young women who experience dysmenorrhea can consume boiled papaya leaves well.